ANALISIS IMPLEMENTASI PENDEKATAN TARL PADA PEMBELAJARAN MATEMATIKA KELAS 5 DI SDN LAKARSANTRI II/473 SURABAYA - Wilujeng, Anisha Tyas; Ganes Gunansyah; Mimyn Putri Muldash (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was motivated by the researcher's interest in the implementation of the Teaching at the Right Level (TaRL) approach in grade 5 mathematics learning at SDN Lakarsantri II/473 Surabaya. Based on several previous studies, there is still a need to examine the implementation of TaRL in mathematics learning at the elementary level so that more educators can apply the TaRL approach. The purpose of this study was to describe the analysis of the implementation of the TaRL approach in grade 5 mathematics learning at SDN Lakarsantri II/473 Surabaya and its supporting and inhibiting factors. The research method used is a qualitative approach with descriptive research design. The results showed that the implementation of the TaRL approach in grade 5 mathematics learning at SDN Lakarsantri II/473 Surabaya has been implemented through the stages of initial assessment, student mapping, preparation of learning designs, and reflection and evaluation. The supporting factors are the support of school leaders, the readiness of trained teachers, and good classroom management skills that have helped the success of the implementation. However, the obstacles are the long preparation time and misconceptions from some parties. Keywords: Implementation, TaRL Approach, Math